Teaching a Foreign Language in Institutions of Higher Education in the Context of Digitalization - Melnyk, Ruslana; Handabura, Oksana; Hlushok, Liudmyla (Pedagogical Discourse, 2024)
The article examines the influence of the digitalization process on the study of foreign languages in an academic educational environment. The following methods were used in the study: a review of the scientific and pedagogical literature on the researched problem, which made it possible to describe and detail the conceptual foundations of the study, to systematize and summarize the theoretical and empirical data used to outline the real state of application of digital technologies in teaching foreighn languages; analysis of the process and products of activity - examples of tasks aimed at the development of various types of competencies of education seekers with the use of ICT are given; the inductive method, according to which scientific research was carried out in the direction «from the analysis of individual material to generalizations and conclusions», and the theoretical foundations were substantiated in detail and illustrated with practical data. The authors analyzed the concept of «digitalization», which is unification of computer, electronic, information, information and communication and telecommunication technologies; focused attention on the latest digital technologies and proposed effective ways of using them at foreign language classes. It was found that ICT competence is one of the priorities in the preparation of future specialists for the high-quality implementation of professional services in the information and digital space, and which implies, in the context of scientific research, the ability of participants of the educational process to use digital resources appropriately when learning foreign languages; the main constituents of ICT competence are defined: general, diagnostic and subject-oriented competences. Examples of tasks aimed at the formation of various types of competences during foreign language learning with the involvement of digital tools are given, and the most common forms of conducting classes using ICT are presented. It is emphasized that digitization modernizes the process of mastering foreign language communicative competence, contributes to more effective and in-depth study of the content of educational material, optimization of the level of self-education of future specialists, ensures their motivation and interaction of all participants of the educational process.